Use of Digital Game-Based Learning, Kahoot! to Improve Students’ English Expressions Mastery - Kadarwati, Sri; Sulistyarini, Ika; Muflikah, Binti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The results of the on-the-ground research revealed that undergraduate students of PGPAUD UPBJJ UT Semarang enrolled in Bahasa Inggris course (PAUD4105) had problems, as evidenced by the course's poor semester test scores, which averaged under 60. Additionally, according to the English tutors, UPBJJ UT Semarang students had significant problems mastering English expressions. They had a very limited understanding of English expressions. As a result, it was necessary to make an effort to overcome this, specifically by establishing relevant, enjoyable, and effective media. This research examined whether game-based learning, Kahoot! could increase students' English expression mastery. The participants in this research were sixth-semester (6) PGPAUD undergraduate research program students at Patebon Pokjar Kendal in the academic year 2019/2020.2. This research was classroom action research with two cycles, a pre-test, and two post-tests. Planning, acting, observing, and reflecting were the four stages of each cycle. Descriptive statistics were used in this investigation. According to the research's findings, the mean pre-test score was 45.95, the average post-test score 1 was 73.35, and the average post-test score 2 was 85.59. In other words, the average score increased by 27.40 points from the pre-test to post-test 1 (from 45.95 to 73.35). Additionally, there was an increase of 12.24 points in the average score from post-test 1 to post-test 2 (from 73.35 to 85.59). Therefore, it could be said that S1 PGPAUD UPBJJ UT Semarang students' mastery of English expressions could be improved by using digital game-based learning, Kahoot!